Affixation in the mental lexicon: morphological priming in russian verbs with orthographic changes - Anastasia Chuprina (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
Suffixed and prefixed words have common linguistic properties and are closely related to the base word in the mental lexicon. Whether different types of information are important for the storage of different types of derivatives or whether their mental organization is similar is one of the topical psycholinguistic questions. My experimental data point at different ways of storing related verbs in the mental lexicon, linked to the base word through two derivational processes. Between the stem and the suffixed relative, the relationship is closer and based on common lexical properties, while the relationship between the stem and the prefix is ??rather formal. I draw this conclusion on the basis of the robust morphological priming effect from the suffixed verb to its base even if the spelling integrity of the suffixed relative is ??violated. This also holds true only in the condition of an orthographically preserved root morpheme. On the contrary, the priming effect to the base verb disappears from a related verb with an orthographically violated prefix. Furthermore, both suffixation and prefixation do not act uniformly and a closer look suggests that lexical organization is modified through the aspectual information of family members. This information will need to be taken into account in future studies of verbal material of the Russian language.